Методика исследования шумовых характеристик для эвольвентного прямозубого зацепления - Бережной, Виталий Александрович; Матюшенко, Николай Васильевич; Федченко, Анна Валерьевна (НТУ "ХПИ", 2015)
Рассматривается методика экспериментального исследования шума для эвольвентных прямозубых передач. Показана актуальность решения данной задачи. Рассмотрены основные понятия и стандарты, необходимые для проведения экспериментальных исследований. Изучаются основные шумовые характеристики передачи: уровень звукового давления, интенсивность звука и акустическая мощность источника. Приводятся основные способы определения акустической мощности машины. Выбирается методика исследования шума редуктора и приводятся основные её положения.

The method of experimental research of noise is examined for involute spur gears. Actuality of decision of this task is proposed. Basic concepts and standards, necessary for the lead through of experimental researches, are considered. Short-story description of different types of noises is Given depending on the type of his source. Basic noise descriptions of transmission are studied: level of voice pressure, intensity of sound and acoustic power of source. The basic base moments of experimental method are selected. Basic methods over of determination of acoustic power of machine are brought. The method of research of noise of reducing gear gets out and its substantive provisions over are brought. The terms of measuring of levels of voice pressure and sound-levels are considered in a reducing gear by sound level meter. The chart of measuring of acoustic power of source of noise is represented round a reducing gear. Conclusions over and list of literature are given.
Research methodology the noise characteristics for spur gear
Keywords: эвольвентная передача; эксперимент; акустическая мощность; звуковое давление; интенсивность звука; involute spur gearing; noise characteristics; experimental methodology; sound power; sound pressure; sound intensity